Negative electrode for lithium secondary battery and method for producing same
By dividing regions in the negative electrode active layer of the lithium secondary battery and applying a magnetic field to orientation the carbon-based negative electrode material, the problems of large volume changes and poor high-speed charging and discharge characteristics during the charging and discharging process are solved, and the problem of high-speed charging and discharge characteristics is realized. High energy density and excellent lifespan characteristics.
Patent Information
- Application Number
- CN202380042686.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-09
- Filing Date
- 2023-12-20
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-12-20
AI Technical Summary
The existing lithium secondary battery negative electrode materials have problems such as large volume changes, poor high-rate charging and discharging characteristics and poor service life characteristics during the charging and discharging process, and it is difficult to achieve high energy density and excellent service life characteristics at the same time.
The carbon-based negative electrode material structure is adopted to divide the central area, edge area and sliding area in the negative electrode active layer, and the carbon-based negative electrode active material is oriented by applying a magnetic field to satisfy the specific alignment ratio and thickness gradient conditions to form Optimized negative electrode active layer.
The negative electrode volume changes small during charging and discharging, excellent high-speed charging and discharging characteristics and high energy density are achieved, and the battery life is extended.
Smart Images

Figure CN119256398A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a negative electrode for a lithium secondary battery and a method for producing the same.
[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0182981 filed on December 23, 2022 and Korean Patent Application No. 10-2023-0017346 filed on February 9, 2023, and the entire contents of the Korean Patent Application are incorporated herein by reference. Background Art
[0003] Recently, secondary batteries have been widely used not only in small devices such as portable electronic devices but also in medium-sized and large devices such as battery packs or energy storage devices in hybrid vehicles or electric vehicles.
[0004] This secondary battery is a power generation device capable of charging and discharging composed of a stacked structure of positive electrode / separator / negative electrode, and generally has a configuration in which the positive electrode includes lithium metal oxide as a positive electrode active material, and the negative electrode includes a carbon-based negative electrode active material such as graphite, so that lithium ions emitted from the positive electrode are adsorbed into the carbon-based negative electrode active material of the negative electrode during charging, and lithium ions included in the carbon-based negative electrode active material are adsorbed into the lithium metal oxide of the positive electrode during discharge, and charging and discharging are repeated.
[0005] In addition, amorphous carbon or crystalline carbon is used as an active material for the negative electrode, and among them, crystalline carbon is mainly used due to its high capacity. These crystalline carbons include natural graphite and artificial graphite.
[0006] Artificial graphite has higher charge and discharge efficiency than natural graphite and expands less during charge and discharge, resulting in better life characteristics. However, compared with natural graphite, it has lower reversible capacity, harder particles, difficulty in rolling when manufacturing electrodes, and poor orientation due to low shape change. In particular, it requires 3000℃ graphitization heat treatment, resulting in high manufacturing costs.
[0007] In addition, natural graphite has been used as a negative electrode active material because it is cheaper than artificial graphite, has a high reversible capacity, and exhibits similar electrochemical performance. However, because natural graphite has a plate-like shape, it has a large surface area and exposed edges, so when electrolyte penetration or decomposition reactions occur, the edges may be delaminated or damaged, resulting in a large irreversible reaction, and the expansion rate increases, resulting in a decrease in long-term life characteristics.
[0008] In addition to these carbon-based negative electrode materials, lithium metal, which has been considered as a negative electrode active material, has very high energy density and can achieve high capacity, but has safety issues and a short cycle life due to dendrite growth (dendrites) during repeated charge and discharge.
[0009] As another negative electrode active material, silicon, tin or their alloys have become the subject of much research in recent years, because it has been recognized that they can reversibly adsorb and release large amounts of lithium through a composite formation reaction with lithium. For example, silicon has a theoretical maximum capacity of about 4020 mAh / g (9800 mAh / cc, specific gravity 2.23), which is very large compared to graphite-based materials, and is therefore promising as a high-capacity negative electrode material. However, the above-mentioned negative electrode active materials have the disadvantages of very large volume changes during charge and discharge, and low high-rate discharge characteristics.
[0010] Therefore, it is necessary to improve the performance of the negative electrode active material to show a low expansion rate, a predetermined capacity, a high output characteristic and a life characteristic. In this regard, a negative electrode active material including a crystalline carbon-based compound such as graphite coated with amorphous carbon is first considered. However, in this case, the energy density is improved, but the proportion of the amorphous carbon-based compound included in the carbon-based negative electrode active material is low, which is not enough to achieve high output characteristics, and in the case where a uniform coating is not formed therein, the life characteristic of the desired level cannot be obtained due to poor conductivity.
[0011] Therefore, various attempts have been made to develop negative electrode active materials with excellent life characteristics by improving high rate charge and discharge characteristics and low expansion ability. A technology that can simultaneously achieve high rate charge and discharge characteristics and high energy density of negative electrode active materials while fundamentally solving these problems is highly desired. Summary of the invention
[0012] Technical issues
[0013] The present invention aims to provide a negative electrode for a lithium secondary battery including a carbon-based negative electrode active material such as natural graphite, which exhibits a small volume change during charge and discharge while exhibiting high rate charge and discharge and high energy density, and a method for manufacturing the same.
[0014] Technical Solution
[0015] In order to solve the above problems,
[0016] In one embodiment, the present invention provides a negative electrode for a lithium secondary battery, comprising:
[0017] a negative electrode current collector; and a negative electrode active layer, the negative electrode active layer being disposed on at least one side of the negative electrode current collector and comprising a carbon-based negative electrode active material,
[0018] Wherein, the negative electrode active layer,
[0019] The negative electrode active layer is divided into a central region including a central portion, a sliding region located at an edge of the negative electrode active layer and having a thickness gradient, and an edge region located between the central region and the sliding region in a width direction of the negative electrode active layer;
[0020] And wherein, the negative electrode for lithium secondary battery satisfies the following formula 1 and formula 2:
[0021] [Formula 1]
[0022] 1.6≤[OI edge ] / [OI center ]≤2.5
[0023] [Formula 2]
[0024] 2.6≤[OI sliding ] / [OI center ]≤3.5
[0025] In equation 1 and equation 2,
[0026] OI edge indicating the degree of alignment (OI) in the edge region,
[0027] OI center indicates the degree of alignment (OI) at the central region, and
[0028] OI sliding Indicates the degree of alignment (OI) in the sliding area,
[0029] And, the alignment degree (OI) indicates the area of the peak representing the [0,0,4] crystal plane in the XRD measurement of the negative electrode active layer (I 004 ) and the area of the peak representing the [1,1,0] crystal plane (I 110 ) ratio (I 004 / I 110 ).
[0030] In this case, the central region of the negative electrode active layer may have an alignment degree (OI) of 0.7 to 1.5. center ).
[0031] Furthermore, the central region of the negative electrode active layer may account for 90% or more of the total length in the width direction of the negative electrode active layer, and the sliding region of the negative electrode active layer may account for 3% or less of the total length in the width direction of the negative electrode active layer.
[0032] In addition, the negative electrode active layer may satisfy the following formula 3:
[0033] [Formula 3]
[0034] R sling <R edge ≤R center
[0035] (In Formula 3,
[0036] R sling Indicates the average thickness of the sliding area,
[0037] R edge indicates the average thickness of the edge region, and
[0038] R center indicates the average thickness of the central region).
[0039] In addition, the central region of the negative electrode active layer may have an average thickness of 100 μm to 300 μm, and the sliding region of the negative electrode active layer may have an inclination angle of 70° or more with respect to an exposed surface of a current collector.
[0040] In addition, the carbon-based negative active material may include one or more of natural graphite and artificial graphite.
[0041] In one embodiment, the present invention also provides a method for manufacturing a negative electrode for a lithium secondary battery, comprising:
[0042] applying a negative electrode slurry including a carbon-based negative electrode active material to a negative electrode current collector;
[0043] applying a magnetic field to the applied negative electrode slurry; and
[0044] Drying the negative electrode slurry to which the magnetic field is applied to form a negative electrode active layer;
[0045] The negative electrode active layer is divided into a central region including a central portion in a width direction of the negative electrode active layer, a sliding region located at an edge of the negative electrode active layer and having a thickness gradient, and an edge region located between the central region and the sliding region, and the negative electrode for a lithium secondary battery satisfies the following formulas 1 and 2:
[0046] [Formula 1]
[0047] 1.6≤[OI edge ] / [OI center ]≤2.5
[0048] [Formula 2]
[0049] 2.6≤[OIsliding ] / [OI center ]≤3.5
[0050] (In Formula 1 and Formula 2,
[0051] OI edge indicating the degree of alignment (OI) in the edge region,
[0052] OI center indicates the degree of alignment (OI) at the central region, and
[0053] OI sliding Indicates the degree of alignment (OI) in the sliding area,
[0054] And, the alignment degree (OI) indicates the area of the peak representing the [0,0,4] crystal plane in the XRD measurement of the negative electrode active layer (I 004 ) and the area of the peak representing the [1,1,0] crystal plane (I 110 ) ratio (I 004 / I 110 )).
[0055] Here, the step of applying a magnetic field applies a magnetic field of 2000 G to 6000 G, and the time for applying the magnetic field may be 5 seconds to 60 seconds.
[0056] In addition, the step of applying the magnetic field may be performed by introducing magnet parts into upper and lower parts of the applied negative electrode slurry, wherein the magnet parts may have a length of 105% to 200% based on a length of the negative electrode slurry in a width direction.
[0057] In addition, the step of forming the negative electrode active layer may include drying the negative electrode slurry; and rolling the dried negative electrode slurry.
[0058] In this case, the edge region of the negative electrode active layer may have a thickness ratio of 90% or more and less than 105% based on an average thickness of the central region of the negative electrode active layer before rolling.
[0059] Beneficial Effects
[0060] The negative electrode for a lithium secondary battery according to the present invention includes a negative electrode active layer divided into a central region, an edge region and a sliding region on a current collector, and has the advantages of exhibiting high-rate charge and discharge and high energy density with small volume change during charge and discharge by satisfying equations 1 and 2 in terms of the alignment degree (OI) of each carbon-based negative electrode active material contained in the central region, the edge region and the sliding region. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 and Figure 2 is an image illustrating a cross-sectional structure of a negative electrode according to the present invention. DETAILED DESCRIPTION
[0062] The present invention can have various modifications and various embodiments, and therefore specific embodiments thereof will be described in detail below.
[0063] However, it should be understood that the present invention is not limited to the specific embodiments, and includes all modifications, equivalents, or substitutes within the spirit and technical scope of the present invention.
[0064] The terms "comprising", "including" and "having" as used herein indicate the presence of characteristics, quantities, steps, actions, components or members, or a combination thereof, described in the specification, and it should be understood that the possibility of the presence or addition of one or more other characteristics, quantities, steps, actions, components, members, or a combination thereof is not precluded.
[0065] In addition, in the present invention, when a part of a layer, film, region, plate, etc. is disposed "on" another part, this includes not only a case where one part is disposed "directly" "on" another part, but also a case where another part is interposed therebetween. Conversely, when a part of a layer, film, region, plate, etc. is disposed "under" another part, this includes not only a case where one part is disposed "directly" "under" another part, but also a case where another part is interposed therebetween. In addition, in the present application, "on" may include not only a case where it is disposed on an upper part, but also a case where it is disposed on a lower part.
[0066] In addition, as used herein, "comprising as a main component" may refer to comprising at least 50 wt% (or at least 50 vol%), at least 60 wt% (or at least 60 vol%), at least 70 wt% (or at least 70 vol%), at least 80 wt% (or at least 80 vol%), at least 90 wt% (or at least 90 vol%), or at least 95 wt% (or at least 95 vol%) of the defined component by total weight (or total volume). For example, "comprising graphite as a main component as a negative electrode active material" may refer to comprising at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 80 wt%, at least 90 wt%, or at least 95 wt% of graphite based on the total weight of the negative electrode active material, and in some cases may refer to the entire negative electrode active material being graphite (including at least 100 wt% of graphite).
[0067] In addition, as used herein, "the carbon-based negative electrode active material is oriented" or "the carbon-based negative electrode active material is aligned" means that the crystal planes of the carbon-based negative electrode active material including the negative electrode active material particles are distributed to have a predetermined orientation relative to the surface of the negative electrode current collector, which may be different from the carbon-based negative electrode active material particles themselves being arranged to have a specific orientation within the negative electrode active layer.
[0068] In addition, “high orientation of carbon-based negative electrode active materials” may refer to that the carbon-based negative electrode active materials contained in the negative electrode active layer are aligned at a high frequency based on the surface of the negative electrode collector, and in some cases, the carbon-based negative electrode active materials contained in the negative electrode active layer are aligned at a large angle based on the surface of the negative electrode collector.
[0069] In addition, "high alignment of the carbon-based negative electrode active material" may mean that the "alignment (OI)" referred to herein has a large value, so that the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a low angle relative to the surface of the negative electrode current collector. On the contrary, "low alignment of the carbon-based negative electrode active material" may mean that the "alignment (OI)" has a small value, which indicates that the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a large angle relative to the surface of the negative electrode current collector.
[0070] Hereinafter, the present invention will be described in more detail.
[0071] Negative electrode for lithium secondary battery
[0072] In one embodiment, the present invention provides a negative electrode for a lithium secondary battery, comprising:
[0073] a current collector including a negative electrode; and a negative electrode active layer disposed on at least one side of the negative electrode current collector and including a carbon-based negative electrode active material,
[0074] Among them, the negative electrode active layer,
[0075] The negative electrode active layer is divided into a central region including a central portion, a sliding region located at an edge of the negative electrode active layer and having a thickness gradient, and an edge region located between the central region and the sliding region in a width direction of the negative electrode active layer;
[0076] The negative electrode for the lithium secondary battery satisfies the following formula 1 and formula 2:
[0077] [Formula 1]
[0078] 1.6≤[OI edge ] / [OI center ]≤2.5
[0079] [Formula 2]
[0080] 2.6≤[OI sliding ] / [OIcenter ]≤3.5
[0081] (In Formula 1 and Formula 2,
[0082] OI edge Indicates the degree of alignment (OI) in the edge area,
[0083] OI center Indicates the degree of alignment (OI) at the central area, and
[0084] OI sliding Indicates the degree of alignment (OI) in the sliding area,
[0085] And the alignment (OI) indicates the area of the peak representing the [0,0,4] crystal plane in the XRD measurement of the negative electrode active layer (I 004 ) and the area of the peak representing the [1,1,0] crystal plane (I 110 ) ratio (I 004 / I 110 )).
[0086] Figure 1 and Figure 2 2 is a cross-sectional view illustrating the structure of negative electrodes 100 and 200 having a negative active layer disposed on one side of a negative current collector according to the present invention.
[0087] The negative electrodes 100 and 200 for lithium secondary batteries according to the present invention include negative electrode active layers 120 and 220 including a carbon-based negative electrode active material on at least one side of the negative electrode collectors 110 and 210. The negative electrode active layers 120 and 220 are layers that embody the electrical activity of the negative electrode, and are prepared by applying a negative electrode slurry including a negative electrode active material that embodies an electrochemical redox reaction to at least one surface of the negative electrode collectors 110 and 210 during charge and discharge of the battery, followed by drying and rolling.
[0088] In this case, the negative electrode active layers 120 and 220 are divided into a central region, an edge region, and a sliding region in the width direction of the negative electrodes 100 and 200. Specifically, the negative electrode active layers 120 and 220 include a central region in the width direction, and the ratio of the central regions 121 and 221 to the total length in the width direction is at least 90%. The central regions 121 and 221 are regions including most of the negative electrode active layers 120 and 220, and may account for a ratio of 93% or more, 95% or more, 97% or more, or 96% to 99% of the total length in the width direction of the negative electrode active layers 120 and 220. As used herein, the term "width direction of the negative electrode active layers 120 and 220" may refer to a direction perpendicular to the direction in which the current collector is driven in the manufacture of the negative electrode, which in some cases may be the same as the direction in which the negative electrode tab is driven from one side of the manufactured negative electrode to the opposite side thereof. The present invention can further increase the power output and energy density of the negative electrode of the lithium secondary battery by adjusting the length ratio of the central regions 121 and 221 in the negative electrode active layers 120 and 220 to the above range.
[0089] Furthermore, the edge regions 122 and 222 are located outside the central regions 121 and 221 , and the sliding regions 123 and 223 are located outside the edge regions 122 and 222 .
[0090] At this time, if Figure 1 As shown, the edge region and the sliding region may be sequentially and continuously disposed on both sides of the central region 121, or, in some cases, due to the fact that the punching (or notching) of the electrode sheet is performed during the negative electrode manufacturing process, they may be Figure 2 The sequence shown is and is arranged continuously on only one side of the central area 221 .
[0091] In addition, the sliding regions 123 and 223 may be regions having a thickness gradient at the edges of the negative electrode active layers 120 and 220, and the ratio of the total length in the width direction of the negative electrode active layers 120 and 220 may be 3% or less. Specifically, the sliding regions 123 and 223 may have a shape in which the thickness decreases outward in the region adjacent to the edge regions 122 and 222, and the ratio of the total length in the width direction of the negative electrode active layers 120 and 220 may be 2% or less, 1% or less, 0.5% or less, 0.01% to 1%, or 0.01% to 0.5% in consideration of the energy density of the negative electrode. In this case, the above-mentioned length ratio is based on the total length ratio arranged in the width direction of the negative electrode active layers 120 and 220, and when the sliding regions 123 and 223 are as shown in FIG. Figure 1 When arranged on both sides of the central area 121 as shown, the length ratio of each sliding area can be reduced to half of the above ratio.
[0092] In addition, the sliding regions 123 and 223 may have a thickness gradient that decreases in thickness as it progresses outward, so that the exposed surface may have a predetermined tilt angle relative to the negative electrode collectors 110 and 210. For example, the sliding regions 123 and 223 may have a tilt angle of 70° or more relative to the negative electrode collectors 110 and 210, so that the exposed surface has a tilt angle of 75° or more, 80° or more, 85° or more, 70° to 85°, 75° to 80°, 70° to 75°. The present invention can prevent the N / P ratio from being reversed at the end of the electrode assembly assembled with the positive electrode by adjusting the tilt angle of the negative electrode collectors 110 and 210 relative to the exposed surface having the sliding regions 123 and 223 to the above range, and can further improve the adhesion with the separator at the negative terminal end.
[0093] In addition, the edge regions 122 and 222 may be used as buffer regions between the central regions 121 and 221 and the sliding regions 123 and 223, and may occupy the remaining length other than the ratio of the lengths of the central regions 121 and 221 and the sliding regions 123 and 223 described above. For example, the edge regions 122 and 222 may have less than 7%, less than 5%, less than 4%, less than 2.5%, 0.09% to 3%, or 0.5% to 1% of the total length in the width direction of the negative electrode active layers 120 and 220. The edge regions 122 and 222 may be arranged on either side of the central region 121 like the sliding regions 123 and 223, so that the length ratio of each edge region may be reduced by half of the above-described length ratio.
[0094] The edge regions 122 and 222 may be located between the central regions 121 and 221 having a constant high load and / or thickness and the sliding regions 123 and 223 having a variable low load and / or thickness, thereby having a constant high or low load and / or thickness configuration.
[0095] In one embodiment, the negative electrode active layers 120 and 220 may satisfy the following Formula 3:
[0096] [Formula 3]
[0097] R sling <R edge ≤R center
[0098] (In Formula 3,
[0099] R sling Indicates the average thickness of the sliding area,
[0100] R edge Indicates the average thickness of the edge area, and
[0101] R centerIndicates the average thickness of the central area).
[0102] Formula 3 shows the correlation between the average thickness of each region, which means that each region of the negative electrode active layer 120 and 220 according to the present invention has a tendency that the average thickness decreases as the position changes from the center to the periphery of the negative electrode active layer 120 and 220. Here, a confocal microscope can be used to measure the "average thickness", and the method of measurement can be different for each region. Specifically, for the central region and the edge region, it may mean measuring the thickness at more than three random points and calculating the average value based on the measured values. In the case of a sliding region, it may mean measuring the thickness of a point where the length of the sliding region is 1 / 2 of the length of the negative electrode active layer 120 and 220 in the width direction.
[0103] For example, the central regions 121 and 221 of the negative active layers 120 and 220 may have an average thickness of 140±3 μm, the edge regions 122 and 222 may have an average thickness of 139±3 μm, and the sliding regions 123 and 223 may have an average thickness of 75±3 μm.
[0104] As another example, the negative electrode active layers 120 and 220 may be such that the average loading per unit area of each region decreases as the position of the negative electrode active layers 120 and 220 changes from the center to the periphery. Here, the average loading per unit area of each region is not limited to the area as long as it is the average loading in the same region.
[0105] By making the negative electrode active layers 120 and 220 of the present invention have an average loading amount per unit area and / or an average thickness per region tending to be as described above, the high-rate charge and discharge characteristics and energy density of the battery including them can be further improved.
[0106] Specifically, the carbon-based negative electrode active material (CA) contained in the negative electrode active layers 120 and 220 may have a crystal plane oriented to have a predetermined angle relative to the surface of the negative electrode current collectors 110 and 210, so that the movement of electrons or lithium ions may be changed according to the orientation degree and / or orientation direction of the negative electrode active material, and the physical-chemical movement of the carbon-based negative electrode active material such as volume expansion or contraction may also be changed. In this case, the crystal plane orientation of the carbon-based negative electrode active material may be achieved by applying a magnetic field to the negative electrode slurry containing the carbon-based negative electrode active material during the manufacture of the negative electrode, and the orientation degree and / or orientation direction may be based on the state or condition of the negative electrode slurry to form the negative electrode active layers 120 and 220. Therefore, the present invention is characterized in that the orientation of the carbon-based negative electrode active material in each region including the negative electrode active layers 120 and 220 may be controlled so that as the loading amount and / or thickness of the negative electrode active layer decreases, the angle of the crystal plane of the carbon-based negative electrode active material contained in the negative electrode active layer decreases.
[0107] For example, the negative electrode active layers 120 and 220 according to the present invention may be oriented such that the average loading amount per unit area and / or the average thickness decreases in the order of the central region, the edge region, and the sliding region, so that the crystal plane angle of the carbon-based negative electrode active material contained in the negative electrode active layers 120 and 220 relative to the surface of the negative electrode current collectors 110 and 210 decreases. In this case, the orientation of the carbon-based negative electrode active material (e.g., graphite) can be determined by crystal plane analysis of the carbon-based negative electrode active material contained in the negative electrode active layer.
[0108] In one embodiment, the negative electrode active layers 120 and 220 may satisfy the following Formula 1 and Formula 2:
[0109] [Formula 1]
[0110] 1.6≤[OI edge ] / [OI center ]≤2.5
[0111] [Formula 2]
[0112] 2.6≤[OI sliding ] / [OI center ]≤3.5
[0113] (In Formula 1 and Formula 2,
[0114] OI edge Indicates the degree of alignment (OI) in the edge area,
[0115] OI center Indicates the degree of alignment (OI) at the central area, and
[0116] OI slidingIndicates the degree of alignment (OI) in the sliding area,
[0117] The alignment degree (OI) indicates the area of the peak representing the [0,0,4] crystal plane in the XRD measurement of the negative electrode active layer (I 004 ) and the area of the peak representing the [1,1,0] crystal plane (I 110 ) ratio (I 004 / I 110 )).
[0118] The orientation degree (OI) of the carbon-based negative electrode active material (CA) can be an indicator of the orientation degree of the crystal structure of the spherical carbon-based negative electrode active material in a specific direction, more specifically, relative to the surface of the negative electrode current collector when measured by X-ray diffraction (XRD). More specifically, the negative electrode active layer has a crystal structure oriented in an orientation manner in the X-ray diffraction measurement, wherein graphite (carbon-based negative electrode active material) has peaks at 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, and 77.5±0.2°, respectively representing the [0,0,2] plane, [1,0,0] plane, [1,0,1]R plane, [1,0,1]H plane, [0,0,4] plane, and [1,1,0] plane. In addition, the peak appearing at 2θ=43.4±0.2° can be regarded as an overlap of peaks corresponding to the [1,0,1]R plane of the carbon-based negative active material (CA) and the [1,1,1] plane of the current collector such as copper (Cu).
[0119] Among them, the degree of alignment (OI) of the carbon-based negative electrode active material (CA) can be measured by the ratio of the area of the peak at 2θ = 54.7 ± 0.2° representing the [0,0,4] plane to the area of the peak at 2θ = 77.5 ± 0.2° representing the [1,1,0] plane, specifically by the ratio of the area obtained by integrating the intensity of the above peaks. Here, since the peak at 2θ = 54.7 ± 0.2° is a peak of the [0,0,4] plane having an inclination with the negative electrode collector among the crystal planes of graphite, the degree of orientation (OI) can mean that when the value is close to 0, the inclination relative to the surface of the negative electrode collector is close to 90°, and when the value is large, the inclination relative to the surface of the negative electrode collector is close to 0° or 180°. In other words, the negative electrode active layer according to the present invention is aligned so that the carbon-based negative electrode active material (CA) has a large angle relative to the negative electrode current collector, such as an angle of more than 60°, more than 70°, 70° to 90°, 80° to 90°, 65° to 85° or 70° to 85° relative to the negative electrode current collector, so that the alignment degree (OI) of the carbon-based negative electrode active material (CA) can be lower than that in the case where the carbon-based negative electrode active material (CA) is aligned at a small angle.
[0120] Taking this into account, Equation 1 indicates that the orientation degree (OI edge ) compared to the alignment degree (OI center ) has a smaller value, which means that the carbon-based negative electrode active material in the central region is aligned at a larger angle relative to the surface of the negative electrode current collector than the carbon-based negative electrode active material in the edge region. The negative electrode active layers 120 and 220 of the present invention allow the carbon-based negative electrode active material in the central region to be aligned at a larger angle relative to the surface of the negative electrode current collector than the carbon-based negative electrode active material in the edge region, so that Formula 1 can satisfy a ratio of 1.6 to 2.5 (in other words, 1.6≤[OI edge ] / [OI center ]≤2.5), and more specifically, 1.7 to 2.0 (ie, 1.7≤[OI edge ] / [OI center ]≤2.0), 1.8 to 2.2 (i.e., 1.8≤[OI edge ] / [OI center ]≤2.2), 2.1 to 2.4 (in other words, 2.1≤[OI edge ] / [OI center ]≤2.4), or 1.7 to 2.3 (in other words, 1.7≤[OI edge ] / [OI center ]≤2.3).
[0121] In addition, Equation 2 indicates that the degree of alignment with the carbon-based negative electrode active material contained in the sliding region (OI sliding ) compared to the alignment degree (OI center ) has a smaller value, which means that the carbon-based negative electrode active material in the central region is aligned at a larger angle relative to the surface of the negative electrode current collector than the carbon-based negative electrode active material in the sliding region. Since the carbon-based negative electrode active material in the central region is aligned at a larger angle relative to the surface of the negative electrode current collector than the carbon-based negative electrode active material in the sliding region, the negative electrode active layers 120 and 220 of the present invention can be 2.6 to 3.5 (2.6≤[OI sliding ] / [OI center ]≤3.5) satisfies the above formula 2, more specifically, 2.6 to 2.9 (2.6≤[OI sliding ] / [OI center]≤2.9), 3.0 to 3.5(3.0≤[O.Isliding] / [O.Icenter]≤3.5), 2.8 to 3.3(2.8≤[O.Isliding] / [O.Icenter]≤3. 3), 3.1 to 3.3 (3.1≤[O.Isliding] / [O.Icenter]≤3.3), or 2.6 to 2.8 (2.6≤[O.Isliding] / [O.Icenter]≤2.8).
[0122] Each region of the negative electrode active layer 120 and 220 may have an alignment degree (OI) of the carbon-based negative electrode active material (CA) satisfying the conditions of Formula 1 and Formula 2 above, so that the average alignment degree of the carbon-based negative electrode active material (CA) contained in the entire negative electrode active layer (120 and 220) may be kept low.
[0123] Specifically, the alignment degree (OI) of the carbon-based negative electrode active material (CA) contained in the central regions 121 and 221 of the negative electrode active layers 120 and 220 is center ) may be 0.7 to 1.5, more specifically 0.7 to 1.3, 0.7 to 1.0, 0.9 to 1.2, or 0.8 to 1.1. In this case, the alignment degree (OI) of the central regions 121 and 221 is center ) may have a deviation of 5% or less from the average alignment of the negative electrode active layers 120 and 220 .
[0124] As described above, the present invention, by adjusting the alignment degree (OI) of the carbon-based negative electrode active material (CA) respectively contained in the central regions 121 and 221, the edge regions 122 and 222 of the negative electrode active layers 120 and 220, and the sliding regions 123 and 223 of the negative electrode active layers 120 and 220 as described above, advantageously has the advantages that the volume change of the negative electrode active layers 120 and 220 during charge and discharge on the current collector is small, the movement of electrons and / or lithium ions inside the negative electrode active layers 120 and 220 is easy, and the electrode resistance is low, thereby improving the high-rate charge and discharge characteristics of the battery.
[0125] In addition, the average thickness of the negative electrode active layers 120 and 220 may be 100 μm to 300 μm, more specifically, 100 μm to 250 μm, 100 μm to 250 μm, or 130 μm to 190 μm, and the average thickness may be the same as the average thickness of the central regions 121 and 221. The present invention can easily control the orientation trend of the carbon-based negative electrode active material contained in each region according to the thickness variation trend by adjusting the average thickness of the negative electrode active layers 120 and 220 to the above range, thereby improving the high-rate charge and discharge characteristics and energy density of the battery including the negative electrodes 100 and 200.
[0126] In addition, depending on the battery model or product application to which the negative electrode according to the present invention is applied, the negative electrode active layers 120 and 220 may have a structure in which two separate layers are stacked, but are not limited thereto. In this case, the negative electrode according to the present invention may have a structure in which a first negative electrode active layer (not shown) is arranged on the current collectors 110 and 210, and a second negative electrode active layer (not shown) is arranged on the first negative electrode active layer. In this case, the first negative electrode active layer and the second negative electrode active layer contain a carbon-based negative electrode active material (CA), but the carbon-based negative electrode active material (CA) contained in each layer may be the same or different.
[0127] In addition, the negative electrode active layers 120 and 220 include a carbon-based negative electrode active material (CA) as a negative electrode active material to achieve electrical activity through a reversible oxidation-reduction reaction during charge and discharge of a battery.
[0128] The carbon-based negative electrode active material (CA) refers to a material having carbon atoms as a main component, and such a carbon-based negative electrode active material (CA) may include graphite. The graphite may include one or more of natural graphite and artificial graphite, but preferably includes natural graphite, or may include a mixture of natural graphite and artificial graphite.
[0129] Preferably, the carbon-based negative electrode active material (CA) is a spherical graphite composition formed by a plurality of flaky graphites. Flaky graphite includes natural graphite, artificial graphite, calcined carbon (blocky mesophase) based on tar and pitch, graphitized coke (raw coke, green coke, pitch coke, needle coke, petroleum coke, etc.), etc., and preferably multiple high-crystallinity natural graphites are used for assembly. In addition, a graphite assembly can be formed by assembling 2 to 100 pieces, preferably 3 to 20 pieces of flaky graphite.
[0130] In addition, the carbon-based negative active material (CA) can present an average particle size (D50) of 0.5μm to 20μm, and more specifically, can present an average particle size (D50) of 0.5μm to 15μm, 0.5μm to 10μm, 5μm to 20μm, 10μm to 20μm, 12μm to 18μm, 2μm to 7μm, 0.5μm to 5μm, or 1μm to 3μm.
[0131] The smaller average particle size of natural graphite can be beneficial to maximize the disorder of each particle in the expansion direction to prevent the particles from expanding due to the charging of lithium ions. However, when the particle size of natural graphite is less than 0.5 μm, a large amount of binder may be required due to the increase in the number of particles per unit volume. On the other hand, when the maximum particle size exceeds 20 μm, the expansion becomes serious, and with the repetition of charge and discharge, the binding properties between particles and the binding properties of particles to the current collector may decrease, and the cycle characteristics may be greatly reduced.
[0132] In addition, the negative electrode active layer according to the present invention may optionally further include a conductive material, a binder, other additives, etc. as needed in addition to the carbon-based negative electrode active material (CA) as a main component.
[0133] The conductive material may include, but is not limited to, one or more of carbon black, acetylene black, ketene black, carbon nanotubes, carbon fibers, and the like.
[0134] As an example, the negative electrode active layer may include carbon black, carbon nanotubes, carbon fibers, etc. as conductive materials, either alone or in combination.
[0135] In this case, the content of the conductive material may be 0.1 to 10 parts by weight in the total 100 parts by weight of the negative electrode active layer, and more specifically, it may be 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, 2 to 6 parts by weight, or 0.5 to 2 parts by weight. The present invention can prevent the problem of the increase of the resistance of the negative electrode due to the low content of the conductive material, resulting in a decrease in the charging capacity, the problem of the decrease of the content of the negative electrode active material due to the excessive conductive material, or the problem of the decrease of the fast charging characteristics due to the increase in the load of the negative electrode active layer by controlling the content of the conductive material within the range as described above.
[0136] In addition, the binder can be appropriately used as a component that helps to connect the negative electrode active material and the conductive material, etc. to the current collector (within the range that it does not reduce the electrical properties of the electrode), specifically, vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile and polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber (SBR) and fluorinated rubber, including one or more selected from the group consisting of them.
[0137] Based on a total of 100 parts by weight of the negative electrode active layer, the content of the binder may be 0.1 to 10 parts by weight, more specifically 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight. The present invention can control the content of the binder contained in the negative electrode active layer within the above range, thereby preventing the adhesiveness of the active layer from being deteriorated due to the low content of the binder, or preventing the electrical properties of the electrode from being reduced due to the excessive amount of the binder.
[0138] In addition, the negative electrode current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, nickel, titanium, calcined carbon, etc. can be used, and in the case of copper or stainless steel, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can also be used. In addition, considering the conductivity and total thickness of the manufactured negative electrode, a negative electrode current collector having an average thickness of 1 μm to 500 μm can be appropriately applied.
[0139] Lithium secondary battery
[0140] In one embodiment, the present invention further provides:
[0141] A lithium secondary battery comprises: an electrode assembly comprising a positive electrode, the negative electrode as described above, and a separator disposed between the positive electrode and the negative electrode.
[0142] The lithium secondary battery according to the present invention includes: an electrode assembly having a plurality of positive electrodes, a separator and a negative electrode each arranged in sequence; and an electrolyte composition having a lithium salt and an electrolyte additive dissolved in a non-aqueous organic solvent. Among them, the lithium secondary battery includes a negative electrode having a structure in which a negative electrode active layer is stacked on a current collector, and the negative electrode active layer is divided into a central region, an edge region and a sliding region, wherein the alignment (OI) of each carbon-based negative electrode active material contained in the central region, the edge region and the sliding region satisfies Formula 1 and Formula 2. Therefore, the lithium secondary battery has the advantage of a small change in the volume of the negative electrode during charge and discharge, and thus exhibits excellent battery life, high-rate charge and discharge characteristics, and high energy density.
[0143] In this case, the negative electrode has the same configuration as described above, and thus a detailed description is omitted.
[0144] In addition, the positive electrode includes a positive electrode active material layer prepared by applying, drying and pressing a slurry including a positive electrode active material on a current collector, and the positive electrode active material layer may optionally further include a conductive material, a binder, other additives, etc. as needed.
[0145] The positive electrode active material is a material capable of electrochemically reacting on a positive electrode current collector, and may include one or more lithium metal oxides capable of reversibly intercalating and deintercalating lithium ions represented by the following Chemical Formula 1 and Chemical Formula 2:
[0146] [Chemical formula 1]
[0147] Li x [Ni y Co z Mn w M 1 v ]O 2
[0148] [Chemical formula 2]
[0149] LiM 2 p Mn q P r O 4
[0150] In the above Chemical Formula 1 and Chemical Formula 2,
[0151] M 1 is at least one element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo,
[0152] x, y, z, w and v are 1.0≤x≤1.30, 0.5≤y<1, 0<z≤0.3, 0<w≤0.3 and 0≤v≤0.1 respectively, where y+z+w+v=1,
[0153] M 2 is Ni, Co or Fe; and
[0154] p is 0.05≤p≤1.0, and
[0155] q is 1-p or 2-p, and
[0156] r is 0 or 1.
[0157] The lithium metal oxides represented by the above Chemical Formula 1 and Chemical Formula 2 are materials containing high contents of nickel (Ni) and manganese (Mn), respectively, and when used as a positive electrode active material, they are compatible with lithium iron phosphate (LiFeO 4 ) and the like, it has the advantage of being able to stably supply high-capacity and / or high-voltage electricity.
[0158] In this case, the lithium metal oxide represented by Chemical Formula 1 may include LiNi0.8 Co 0.1 Mn 0.1 O 2 、LiNi 0.6 Co 0.2 Mn 0.2 O 2 、LiNi 0.9 Co 0.05 Mn 0.05 O 2 、LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O 2 、LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O 2 、LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O 2 etc., and the lithium metal oxide represented by Chemical Formula 2 may include LiNi 0.7 Mn 1.3 O 4 、LiNi 0.5 Mn 1.5 O 4 、LiNi 0.3 Mn 1.7 O 4 、LiFePO 4 、LiFe q Mn 1-q PO 4 etc., and these may be used alone or in combination.
[0159] In addition, the positive electrode active material may account for 85 parts by weight or more of the positive electrode active material layer, and more specifically, it may account for 90 parts by weight or more, 93 parts by weight or more, or 95 parts by weight or more.
[0160] In addition, the positive electrode active material layer may further include a conductive material, a binder, other additives, etc. as well as the positive electrode active material.
[0161] In this case, the conductive material can be used to improve the electrical properties of the positive electrode, and the conductive materials conventionally used in the art can be applied, but can specifically include at least one type selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Denka black, Ketjen black, Super P, channel black, furnace black, lamp black, summer black, graphene and carbon nanotubes.
[0162] In addition, the conductive material may account for 0.1 to 5 parts by weight of each positive active layer, more specifically, 0.1 to 4 parts by weight; 2 to 4 parts by weight; 1.5 to 5 parts by weight; 1 to 3 parts by weight; 0.1 to 2 parts by weight; or 0.1 to 1 part by weight.
[0163] In addition, the binder is used to bind the positive active material, the positive electrode additive and the conductive material to each other, and can be used without restriction as long as it has this function. Specifically, the binder may include one or more resins selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile, polymethyl methacrylate and copolymers thereof. In one embodiment, the binder may include polyvinylidene fluoride.
[0164] In addition, the binder may account for 1 to 10 parts by weight, more specifically 2 to 8 parts by weight; or 1 to 5 parts by weight per positive electrode active layer.
[0165] The total thickness of the positive electrode active layer is not particularly limited, but may be 50 to 300 μm, more specifically 100 to 200 μm, 80 to 150 μm, 120 to 170 μm, 150 to 300 μm, 200 to 300 μm, or 150 to 190 μm.
[0166] In addition, as the positive electrode, a positive electrode current collector having high conductivity without causing chemical changes in the battery can be used. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. can be used, and in the case of aluminum or stainless steel, aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can also be used. In addition, considering the conductivity and total thickness of the positive electrode to be manufactured, the average thickness of the above-mentioned current collector can be appropriately applied to 3μm to 500μm.
[0167] In addition, the separator interposed between the positive electrode and the negative electrode of each unit cell is an insulating film with high ion permeability and mechanical strength, and is not particularly limited to those conventionally used in the art, but in particular, a polymer including one or more polypropylene, polyethylene and polyethylene-propylene copolymer having chemical resistance and hydrophobicity can be used. The separator may have the form of a porous polymer substrate such as a sheet or non-woven fabric including the above-mentioned polymer, and in some cases, it may also have the form of a composite separator in which organic particles or inorganic particles are coated on a porous polymer substrate by an organic binder. In addition, the separator may have an average pore size of 0.01 μm to 10 μm and an average thickness of 5 μm to 300 μm.
[0168] In addition, the lithium secondary battery according to the present invention can be a secondary battery of any shape, including but not limited to a stacked type, a zigzag type or a zigzag stacked type electrode assembly. As an embodiment, the lithium secondary battery according to the present invention can be a pouch type secondary battery or a square secondary battery.
[0169] Negative electrode manufacturing method
[0170] In one embodiment, the present invention also provides a method for manufacturing a negative electrode for a lithium ion battery, comprising:
[0171] applying a negative electrode slurry including a carbon-based negative electrode active material to a negative electrode current collector;
[0172] applying a magnetic field to the applied negative electrode slurry; and
[0173] The negative electrode slurry to which the magnetic field is applied is dried to form a negative electrode active layer.
[0174] The negative electrode active layer is divided into a central region including a central portion in the width direction of the negative electrode active layer, a sliding region located at the edge of the negative electrode active layer and having a thickness gradient, and an edge region located between the central region and the sliding region; and the negative electrode for a lithium secondary battery satisfies the following formulas 1 and 2:
[0175] [Formula 1]
[0176] 1.6≤[OI edge ] / [OI center ]≤2.5
[0177] [Formula 2]
[0178] 2.6≤[OI sliding ] / [OI center ]≤3.5
[0179] (In Formula 1 and Formula 2,
[0180] OI edge Indicates the degree of alignment (OI) in the edge area,
[0181] OI center Indicates the degree of alignment (OI) at the central area, and
[0182] OI sliding Indicates the degree of alignment (OI) in the sliding area,
[0183] The alignment degree (OI) indicates the area of the peak representing the [0,0,4] crystal plane in the XRD measurement of the negative electrode active layer (I 004 ) and the area of the peak representing the [1,1,0] crystal plane (I 110 ) ratio (I004 / I 110 )).
[0184] The method for manufacturing a negative electrode according to the present invention may include applying a negative electrode slurry including a carbon-based negative electrode active material to a current collector, and by applying a magnetic field to the surface of the applied negative electrode slurry, the carbon-based negative electrode active material in the negative electrode slurry may be aligned to have a predetermined angle relative to the surface of the current collector. Subsequently, the negative electrode may be manufactured by drying the negative electrode slurry in which the alignment of the carbon-based negative electrode active material is reduced to form a negative electrode active layer.
[0185] Here, applying the negative electrode slurry is to coat the surface of the mobile current collector by discharging the negative electrode slurry containing the carbon-based negative electrode active material, and can be applied in any manner conventionally used in the art without being particularly limited, but preferably a die coating method can be used. The die coating method can be performed with the aid of a slit die head having a gasket for controlling the discharge conditions of the negative electrode slurry. In this case, by controlling the shape of the gasket, etc., the load amount, application thickness, etc. of the negative electrode slurry applied to the current collector can be easily controlled.
[0186] In addition, applying a magnetic field to the negative electrode slurry can be to orient the crystal plane of the carbon-based negative electrode active material contained in the negative electrode slurry to have a predetermined angle relative to the current collector. To this end, the applied magnetic field can be applied by a magnet portion disposed on the upper and lower portions of the negative electrode current collector (moved by applying the negative electrode slurry on its surface).
[0187] In this case, the degree of alignment (OI) of the carbon-based negative active material contained in the negative electrode slurry may be adjusted by the applied magnetic field strength or the time of exposure to the magnetic field, and thus, applying the magnetic field may be performed under predetermined magnetic field strength and time conditions.
[0188] Specifically, the applied magnetic field can apply a magnetic field of 2000G (Gauss) to 6000G (Gauss), and more specifically, the magnetic field can be applied with a strength of 2500G to 5500G, 3000G to 5500G, 3500G to 5500G, 4000G to 5500G, 3500G to 4500G, or 4500G to 5000G.
[0189] In addition, applying the magnetic field may be performed for a period of 5 seconds to 60 seconds, more specifically, 10 seconds to 60 seconds, 10 seconds to 30 seconds, 30 seconds to 60 seconds, 40 seconds to 50 seconds, 15 seconds to 35 seconds, or 10 seconds to 50 seconds.
[0190] In one embodiment, applying the magnetic field may include applying a magnetic field of 4700±100 G to the negative electrode slurry for 12 seconds to 33 seconds.
[0191] In addition, as described above, the application of the magnetic field can be performed by the magnet part introduced into the upper and lower parts of the applied negative electrode slurry, but the size of the magnet part can be adjusted to be larger than the size of the negative electrode slurry so that the magnetic field applied to the negative electrode slurry can be uniformly applied to the entire surface of the negative electrode slurry. For example, based on the ratio of the width to the length of the negative electrode slurry, the magnet part can have a length ratio of 105% to 200%, and more specifically, based on the ratio of the width to the length of the negative electrode slurry, it can have a length ratio of 110% to 180%, 110% to 160%, 110% to 140%, 110% to 130%, 130% to 150%, or 105% to 120%.
[0192] The present invention can control the domain orientation of the carbon-based negative active material contained in the negative electrode slurry to satisfy Formula 1 and Formula 2 by controlling the magnetic field strength, application time and / or magnet part size as described above in the step of applying the magnetic field.
[0193] In addition, forming the negative electrode active layer may include: drying the negative electrode slurry; and rolling the dried negative electrode slurry.
[0194] In this case, drying the negative electrode slurry may be applied in any manner capable of maintaining the orientation of the carbon-based negative electrode active material included in the negative electrode active layer without particular limitation.
[0195] For example, the drying may be performed by applying thermal energy to the negative electrode slurry using a hot air dryer, a vacuum oven, or the like to dry the negative electrode slurry.
[0196] In addition, rolling the dried negative electrode slurry is to increase the density of the negative electrode active layer by applying pressure to the dried negative electrode slurry using a roller press, etc. At this time, the rolling may be performed under a temperature condition higher than room temperature.
[0197] Specifically, the rolling may be performed at a temperature of 50% to 100%, more specifically, at a temperature of 60°C to 100°C, 75°C to 100°C, 85°C to 100°C, 50°C to 90°C, 60°C to 80°C, or 65°C to 90°C. More specifically, rolling can be performed at a rolling speed of 2m / s to 7m / s, and more specifically, rolling can be performed at a rolling speed of 2m / s to 6.5m / s, 2m / s to 6m / s, 2m / s to 5.5m / s, 2m / s to 5m / s, 2m / s to 4.5m / s, 2m / s to 4m / s, 2.5m / s to 4m / s, 2.5m / s to 3.5m / s, 3.5m / s to 5m / s, 5m / s to 7m / s, 5.5m / s to 6.5m / s, or 6m / s to 7m / s. In addition, the rolling may be performed under a pressure condition of 50 MPa to 200 MPa, more specifically, 50 MPa to 150 MPa, 50 MPa to 100 MPa, 100 MPa to 200 MPa, 150 MPa to 200 MPa, or 80 MPa to 140 MPa.
[0198] The present invention can perform rolling of the dried negative electrode slurry under the above-mentioned temperature, speed and / or pressure conditions, thereby increasing the energy density of the negative electrode while minimizing the change in the alignment of the carbon-based negative electrode active material included in the formed negative electrode active layer.
[0199] In addition, the average thickness of the edge region may be equal to or less than the average thickness of the central region before rolling, and therefore, the negative electrode slurry loading in the edge region may be equal to or less than the negative electrode slurry loading in the central region. Specifically, based on the average thickness of the central region of the negative electrode active layer before rolling, the edge region of the negative electrode active layer may have a thickness ratio greater than 90% and less than 105%. More specifically, based on the average thickness of the central region before rolling, the edge region may be 95% to 100%, 98% to 102%, or 97% to 100%.
[0200] Invention Mode
[0201] Hereinafter, the present invention will be described in more detail through embodiments and experimental examples.
[0202] However, the following Examples and Experimental Examples merely illustrate the present invention, and the present invention is not limited to the following Examples and Experimental Examples.
[0203] Examples 1 to 3 and Comparative Examples 1 to 3. Preparation of negative electrode for lithium secondary battery
[0204] A negative electrode for a lithium secondary battery was prepared by reflecting the conditions shown in Table 1 below.
[0205] First, natural graphite (average particle size: 10±1 μm) and artificial graphite (average particle size: 8±1 μm) were prepared as carbon-based negative electrode active materials, respectively, and negative electrode slurry was prepared using the prepared carbon-based negative electrode active materials.
[0206] Specifically, the negative electrode active material is prepared by mixing natural graphite and artificial graphite in a weight ratio of 1 to 3:7 to 9, and carbon black as a conductive material and carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) as a binder. Then, a negative electrode slurry is prepared by mixing 95 parts by weight of the mixed graphite, 1 part by weight of carbon black, 1.5 parts by weight of carboxymethyl cellulose (CMC) and 2.5 parts by weight of styrene butadiene rubber (SBR) with water to prepare 50% solid.
[0207] Once the negative electrode slurry was prepared, the negative electrode slurry was cast on a copper sheet (thickness: 10 μm) using a die coater under roll-to-roll transmission (transmission speed: 5 m / min). At this time, the negative electrode slurry was cast so that the average thickness along the transmission direction of the copper sheet was 190 μm, and by changing the shape of the gasket set in the die coater, the average thickness of each area of the negative electrode active layer after rolling was controlled as shown in Table 1.
[0208] Then, a permanent magnet having a length ratio of 110% to 120% based on the length in the width direction of the applied negative electrode slurry is located in the upper part of the applied negative electrode slurry and the lower part of the current collector, and a magnetic field of 4700±100G is applied for 15 seconds, and the negative electrode slurry with the applied magnetic field is thermally dried to form a negative electrode active layer. The formed negative electrode active layer is rolled at 50±1°C, a pressure of 100MPa to 150MPa, and a transmission speed of 3m / s to prepare a film having a thickness of 100 to 1500mm. Figure 1 A negative electrode for a lithium secondary battery having a cross-sectional structure shown.
[0209] For each negative electrode active layer of the prepared negative electrode, a region having a length ratio of 98.5% based on the length in the width direction of the negative electrode active layer at the center was set as a central region, and regions (each having a length ratio of 0.5%) set at a total length ratio of 1.0% on both sides of the central region were set as edge regions. Then, regions with a length ratio of 0.5% (each having a length ratio of 0.25%) outside the edge region were set as sliding regions.
[0210] Then, the average thickness of each set area was measured, and the results are shown in the following Table 1. In this case, the average thickness of the central area and the edge area of the negative electrode active layer was obtained by measuring the confocal thickness of each area three times and calculating the average value thereof; and the sliding area of the negative electrode active layer was defined as the average thickness of the point where the sliding area length in the width direction was 1 / 2 of the length of the negative electrode active layer.
[0211] In addition, X-ray diffraction spectroscopy (XRD) was performed on each region of the negative electrode active layer to measure the spectrum. The measurement conditions of X-ray diffraction (XRD) were as follows:
[0212] -Target: Cu (Kα line) graphite monochromator
[0213] - Slits: Divergence slit = 1 degree, Receiving slit = 0.1 mm, Scattering slit = 1 degree
[0214] - Measurement area: [1,1,0] plane: 76.5 degrees < 2θ < 78.5 degrees / [0,0,4] plane: 53.5 degrees < 2θ < 56.0 degrees.
[0215] From the spectrum measured under the above conditions, the corresponding areas of the peak representing the [0,0,4] crystal plane and the peak representing the [1,1,0] crystal plane were calculated, and the ratio of these areas (I 004 / I 110 ) to obtain the alignment index (OI) of the mixed graphite by region. The calculated values are shown in Table 1 below.
[0216] [Table 1]
[0217]
[0218]
[0219] Comparative Examples 4 and 5. Preparation of negative electrode for lithium secondary battery
[0220] A negative electrode for a lithium secondary battery was prepared by the same method as in Example 2, except that a magnetic field was not applied after casting of the negative electrode slurry, or a magnetic field was applied using a permanent magnet having a length ratio of 95% to 100% based on the length in the width direction of the negative electrode slurry.
[0221] The manufactured negative electrode was measured for the average thickness of each region of the negative electrode active layer and the degree of alignment (OI) of the carbon-based negative electrode active material by the same method as in Example 2, and the measurement results are shown in Table 2 below.
[0222] [Table 2]
[0223]
[0224] Examples 4 to 6 and Comparative Examples 6 to 10. Production of Lithium Secondary Batteries
[0225] By preparing LiNi with a particle size of 5 μm 0.7 Co 0.1 Mn 0.1 Al 0.1 O 2As a positive electrode active material, it was mixed with polyvinylidene fluoride as a carbon-based conductive agent and a binder in a weight ratio of 94:3:3 in N-methylpyrrolidone (NMP) to form a slurry, which was cast on an aluminum sheet, dried in a vacuum oven at 120°C and rolled to prepare a positive electrode.
[0226] Separators including 18 μm polypropylene were interposed between the above positive electrodes and negative electrodes prepared in Examples 1 to 3 and Comparative Examples 1 to 3 and 5, respectively, and lithium secondary batteries were assembled by inserting them into a case and then injecting the electrolyte composition.
[0227] At this time, the type of negative electrode applied to each lithium secondary battery is indicated in Table 3 below.
[0228] [Table 3]
[0229] Type of negative electrode applied Example 4 The negative electrode prepared in Example 1 Example 5 The negative electrode prepared in Example 2 Example 6 The negative electrode prepared in Example 3 Comparative Example 6 The negative electrode prepared in Comparative Example 1 Comparative Example 7 The negative electrode prepared in Comparative Example 2 Comparative Example 8 The negative electrode prepared in Comparative Example 3 Comparative Example 9 The negative electrode prepared in Comparative Example 4 Comparative Example 10 The negative electrode prepared in Comparative Example 5
[0230] Experimental example.
[0231] The following experiments were performed to evaluate the performance of the negative electrode according to the present invention.
[0232] a) Evaluation of negative electrode thickness expansion characteristics
[0233] The lithium secondary batteries prepared in Examples 4 to 6 and Comparative Examples 6 to 10 were charged and discharged 30 times at a 0.5C rate and then recharged to disassemble the battery in a fully charged (SOC 100%) state. After collecting the negative electrode from the disassembled battery, it was washed with diethyl carbonate (DEC) and dried to analyze the thickness expansion rate of the negative electrode after charging and discharging. The results are shown in Table 4.
[0234] b) Evaluation of high-rate charging performance
[0235] The lithium secondary batteries prepared in Examples 4 to 6 and Comparative Examples 6 to 10 were charged to a point of 80% SOC by applying a current at a 3.0C rate, and the voltage change and dV / dQ according to the SOC were measured. If there is a voltage platform in the measured voltage change, or if the graph of dV / dQ is bimodal, lithium is identified as precipitated from the negative electrode surface. In addition, the corresponding SOC value at which lithium is identified as precipitated is defined as the maximum SOC value at which the secondary battery can be quickly charged, and is measured. The results are shown in Table 4 below.
[0236] c) Evaluation of high rate discharge performance
[0237] For the lithium secondary batteries prepared in Examples 4 to 6 and Comparative Examples 6 to 10, the capacity was measured when the lithium secondary batteries were buffered to 0.5C rate (SOC 100%) and the buffered lithium secondary batteries were discharged to 1.5V at 0.1C rate. Then, each lithium secondary battery was buffered again at 0.5C rate (SOC 100%) and discharged to 1.5V at 2.0C rate. The charge and discharge process was repeated 100 times, and the capacity at 0.1C rate discharge was calculated based on the capacity at 2.0C rate, and the capacity retention rate after 100 discharges was calculated, and the results are shown in Table 4 below. If the calculated percentage of the initial charge capacity is greater than 85%, it is marked as "○", if the percentage of the initial charge capacity is less than 80%, it is marked as "X", and if the percentage of the initial charge capacity is greater than 80% but less than 85%, it is marked as "△".
[0238] [Table 4]
[0239]
[0240] As shown in Table 4 above, it can be seen that the negative electrode for a lithium secondary battery according to the present invention has less negative electrode thickness expansion during charge and discharge and has excellent output performance.
[0241] Specifically, it was found that the lithium secondary battery manufactured in the embodiment had a low thickness expansion rate of the negative electrode of less than 25% after charge and discharge, and when charged at a high rate of 3.0C rate, lithium plating occurred later than the secondary battery manufactured in the comparative example, and the SOC of lithium precipitation was higher than 40%. In addition, it was found that the above lithium secondary battery had a capacity retention rate of more than 85% when discharged 100 times at a high rate of 2.0C rate.
[0242] This means that the negative electrode of the embodiment has a configuration in which the alignment order (OI) of each carbon-based negative electrode active material contained in the central region, edge region and sliding region of the negative electrode active layer satisfies Formula 1 and Formula 2, thereby further reducing the volume change of the negative electrode during charge and discharge of the secondary battery, and further improving the accessibility of lithium ions in the negative electrode active layer, thereby improving the high rate characteristics.
[0243] From these results, it can be seen that the negative electrode for a lithium secondary battery according to the present invention exhibits a small volume change during charge and discharge, excellent high-rate charge and discharge performance, and high energy density.
[0244] As described above, the present invention has been described in more detail by way of example. However, since the configuration described in the embodiments described herein is only one embodiment of the present invention and does not represent the overall technical concept of the present invention, it should be understood that the present invention encompasses various equivalents, modifications and substitutions when submitting this application.
[0245] Therefore, the technical scope of the present invention is not limited to the contents described in the detailed description of the specification, but should be determined by the patent claims.
[0246] [Explanation of Reference Numerals]
[0247] 100 and 200: Negative electrode for lithium secondary battery according to the present invention
[0248] 110 and 210: negative electrode current collector
[0249] 120 and 220: Negative active layer
[0250] 121 and 221: Central area of the negative electrode active layer
[0251] 122 and 222: Edge area of the negative electrode active layer
[0252] 123 and 223: Sliding area of the negative electrode active layer
[0253] CA: Carbon-based negative electrode active materials
[0254] ↑: Alignment direction of the crystal plane of carbon-based negative electrode active materials
Claims
1. A negative electrode for a lithium secondary battery, the negative electrode for a lithium secondary battery comprising: Anode current collector; and a negative electrode active layer disposed on at least one side of the negative electrode current collector and comprising a carbon-based negative electrode active material, wherein the negative electrode active layer is divided into a central region including a central portion, a sliding region located at an edge of the negative electrode active layer and having a thickness gradient, and an edge region located between the central region and the sliding region in a width direction of the negative electrode active layer; And wherein, the negative electrode for lithium secondary battery satisfies the following formula 1 and formula 2: [Formula 1] 1.6≤[OI edge ] / [OI center ]≤2.5 [Formula 2] 2.6≤[OI sliding ] / [OI center ]≤3.5 In equation 1 and equation 2, OI edge indicating the degree of alignment (OI) in the edge region, OI center indicates the degree of alignment (OI) at the central region, and OI sliding Indicates the degree of alignment (OI) in the sliding area, And, the alignment degree (OI) indicates the area of the peak representing the [0,0,4] crystal plane in the XRD measurement of the negative electrode active layer (I 004 ) and the area of the peak representing the [1,1,0] crystal plane (I 110 ) ratio (I 004 / I 110 ).
2. The negative electrode for a lithium secondary battery according to claim 1, wherein The central region of the negative electrode active layer has an alignment degree (OI) of 0.7 to 1.
5. center ).
3. The negative electrode for a lithium secondary battery according to claim 1, wherein The ratio of the central region of the negative electrode active layer to the total length in the width direction of the negative electrode active layer is 90% or more, Furthermore, a ratio of the sliding region of the negative electrode active layer to a total length in a width direction of the negative electrode active layer is 3% or less.
4. The negative electrode for a lithium secondary battery according to claim 1, wherein The negative electrode active layer satisfies the following formula 3: [Formula 3] R sling <R edge ≤R center In formula 3, R sling Indicates the average thickness of the sliding area, R edge indicates the average thickness of the edge region, and R center The average thickness of the central region is indicated.
5. The negative electrode for a lithium secondary battery according to claim 1, wherein The central region of the negative electrode active layer has an average thickness of 100 μm to 300 μm.
6. The negative electrode for a lithium secondary battery according to claim 1, wherein The carbon-based negative electrode active material includes one or more of natural graphite and artificial graphite.
7. A method for manufacturing a negative electrode for a lithium secondary battery, the method comprising the following steps: applying a negative electrode slurry including a carbon-based negative electrode active material to a negative electrode current collector; applying a magnetic field to the applied negative electrode slurry; and Drying the negative electrode slurry to which the magnetic field is applied to form a negative electrode active layer; The negative electrode active layer is divided into a central region including a central portion in a width direction of the negative electrode active layer, a sliding region located at an edge of the negative electrode active layer and having a thickness gradient, and an edge region located between the central region and the sliding region, and the negative electrode for a lithium secondary battery satisfies the following formulas 1 and 2: [Formula 1] 1.6≤[OI edge ] / [OI center ]≤2.5 [Formula 2] 2.6≤[OI sliding ] / [OI center ]≤3.5 In equation 1 and equation 2, OI edge indicating the degree of alignment (OI) in the edge region, OI center indicates the degree of alignment (OI) at the central region, and OI sliding Indicates the degree of alignment (OI) in the sliding area, And, the alignment degree (OI) indicates the area of the peak representing the [0,0,4] crystal plane in the XRD measurement of the negative electrode active layer (I 004 ) and the area of the peak representing the [1,1,0] crystal plane (I 110 ) ratio (I 004 / I 110 ).
8. The method for producing a negative electrode for a lithium secondary battery according to claim 7, wherein: The step of applying a magnetic field applies a magnetic field of 2000 G to 6000 G.
9. The method for producing a negative electrode for a lithium secondary battery according to claim 7, wherein: The magnetic field is applied for a period of 5 to 60 seconds.
10. The method for producing a negative electrode for a lithium secondary battery according to claim 7, wherein: The step of applying the magnetic field is performed by introducing magnet parts into upper and lower parts of the applied negative electrode slurry, wherein the magnet parts have a length of 105% to 200% based on a length of the negative electrode slurry in a width direction.
11. The method for producing a negative electrode for a lithium secondary battery according to claim 7, wherein: The step of forming the negative electrode active layer includes: drying the negative electrode slurry; and rolling the dried negative electrode slurry.
12. The method for producing a negative electrode for a lithium secondary battery according to claim 11, wherein: The edge region of the negative electrode active layer has a thickness ratio of 90% or more and less than 105% based on an average thickness of the central region of the negative electrode active layer before rolling.
Citation Information
Patent Citations
Interface device with three-dimensional (3-D) viewing function
KR1020230017346A
Secondary battery
CN108807959A
Negative plate and application thereof
CN113066954A
Secondary battery and device containing same
CN113228341A
Power storage device and method for manufacturing lithium ion secondary cell
CN113950756A
